ADUBAÇÃO NITROGENADA E MOLÃBDICA NA CULTURA DO FEIJÃO - Vieira, Clibas; Nogueira, Afrânio Otávio; Araújo, Geraldo A. de A. (REVISTA DE AGRICULTURA, 2015)
ADUBAÇÃO NITROGENADA E MOLÃBDICA NA CULTURA DO FEIJÃO